ECRANIZATION OF RENTANG KISAH FILM DIRECTED BY DANIAL RIFKI - Purwanto, Joko; Nanda Saputri, Utari; Basuki, Basuki (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This research is motivated by the lack of research on literary criticism, especially the study of ecranization. Based on these problems, the purpose of this study is to describe the ecranization of Rentang Kisah film by director Danial Rifki. This research method is comparative descriptive with content analysis. The data sources for this research are Rentang Kisah novel by Gita Savitri Devi and Rentang Kisah film by director Danial Rifki. The research instrument is the researcher himself with the help of data recording cards and writing instruments. Data collection techniques are observation techniques and note-taking techniques. Research stages: reading, listening, identifying, taking notes, and classifying. The results of the analysis show that the ecranization process includes: shrinking includes shrinking the setting and setting of the atmosphere; and addition includes adding characters and time setting.